Treatment of Disseminated Aspergillosis with Posaconazole in 10 Dogs. (14th November 2015) - Corrigan, V.K.; Legendre, A.M.; Wheat, L.J.; Mullis, R.; Johnson, B.; Bemis, D.A.; Cepero, L.
Abstract : Background: Few effective treatments for disseminated Aspergillus infections in dogs are available. Posaconazole has potent and broad‐spectrum activity against Aspergillus spp ., but its use has not yet been sufficiently evaluated in dogs. Hypothesis/Objectives: The aim of this study was to determine the safety and efficacy of posaconazole for the treatment of naturally occurring disseminated Aspergillus infections in dogs. Animals: Ten client‐owned dogs with disseminated aspergillosis. Methods: Prospective, nonrandomized, noncontrolled study with posaconazole administered to dogs at dosage of 5 mg/kg PO q12h. The primary veterinarian or the veterinary specialist caring for the dogs provided patient data. Results: The treatment response for dogs with disseminated disease while receiving posaconazole was defined as clinical remission (n = 4) and clinical improvement (n = 6). There was a high rate of relapse during treatment or after cessation of treatment in both groups, and most dogs died or were euthanized due to progressive disease. Excluding 1 dog concurrently treated with terbinafine that remains alive 5 years after diagnosis, the mean survival time for dogs was 241 days (range 44–516 days). Three other dogs lived >1 year after starting treatment. No clinically relevant adverse events or increases in serum liver enzyme activity occurred during treatment with posaconazole. Conclusions and Clinical Importance: Posaconazole appears to be safe and well‐tolerated for treatment of disseminated Aspergillus infections in dogs. Long‐term survival >1 year is possible with prolonged treatment, but relapse is common.